CSUSM Trans & Gender Non-Conforming Task Force Report & Recommendations - Booth, Char; Anbar, Zev; Read, Betsy; Robertson-Howell, Jay; Blanshan, Bridget; Dayhoff, Wesley; Dockstader, Jessica; Elsbree, Anne Rene; McLean, Lisa; Medina, Lisa; Morton, Deborah; Ramirez, Steve
In May of 2016, members of the California State University San Marcos (CSUSM) community issued an open letter to President Karen Haynes advocating for actions to encourage the inclusion of trans and gender non-conforming individuals at CSUSM. In November of 2016, President Haynes issued a call for participation in a Trans and Gender Non-Conforming Task Force (TGNCTF) "in an effort to ensure ongoing support for members of our Trans and Gender Non-Conforming community at Cal State San Marcos." The TGNCTF was convened in December 2016 as advisory to the President, and by March 17th, 2017 was charged to "Review and make recommendations regarding protocols, programs and services for CSUSM Trans and Gender Non-Conforming Communities to include: Preferred Name Policy Implementation; Restrooms; Training; Housing. Your participation and knowledge will greatly benefit the University and the goals we are working to achieve, which include providing an open, welcoming and safe environment all members of our community." In response to this charge, the TGNCTF is pleased to provide an overview of the current status of policies, procedures, and actions relevant to trans and gender non-conforming communities at CSUSM, and to provide recommendations to further improve the environment and experience of our trans students, staff, and faculty. We do so from a variety of perspectives, including those of trans-identified and trans-allied task force (TF) members, trans and allied communities at CSUSM, and stakeholders critical to the implementation of these recommendations. Careful consideration was given to federal and state law, as well as best practice guidance from organizations dedicated to trans advocacy.